Axotomy Induces Phasic Alterations in Luman/CREB3 Expression and Nuclear Localization in Injured and Contralateral Uninjured Sensory Neurons: Correlation With Intrinsic Axon Growth Capacity. Issue 4 (12th March 2019) - Hasmatali, Jovan C D; De Guzman, Jolly; Zhai, Ruiling; Yang, Lisa; McLean, Nikki A; Hutchinson, Catherine; Johnston, Jayne M; Misra, Vikram; Verge, Valerie M K
Abstract: Luman/CREB3 is an important early retrograde axotomy signal regulating acute axon outgrowth in sensory neurons through the adaptive unfolded protein response. As the injury response is transcriptionally multiphasic, a spatiotemporal analysis of Luman/CREB3 localization in rat dorsal root ganglion (DRG) with unilateral L4–L6 spinal nerve injury was conducted to determine if Luman/CREB3 expression was similarly regulated. Biphasic alterations in Luman/CREB3 immunofluorescence and nuclear localization occurred in neurons ipsilateral to 1-hour, 1-day, 2-day, 4-day, and 1-week injury, with a largely parallel, but less avid response contralaterally. This biphasic response was not observed at the transcript level. To assess whether changes in neuronal Luman expression corresponded with an altered intrinsic capacity to grow an axon/neurite in vitro, injury-conditioned and contralateral uninjured DRG neurons underwent a 24-hour axon growth assay. Two-day injury-conditioned neurons exhibited maximal outgrowth capacity relative to naïve, declining at later injury-conditioned timepoints. Only neurons contralateral to 1-week injury exhibited significantly higher axon growth capacity than naïve. In conclusion, alterations in neuronal injury-associated Luman/CREB3 expression support that a multiphasic cell body response occurs and reveal a novel contralateral plasticity in axon growth capacity at 1-week post-injury. These adaptive responses have the potential to inform when repair or therapeutic intervention may be most effective.